Adverse effects in patients with acute falciparum malaria treated with artemisinin derivatives. - Price, R; van Vugt, M; Phaipun, L; Luxemburger, C; Simpson, J; Mcgready, R; ter Kuile, F; Kham, A; Chongsuphajaisiddhi, T; White, N; Nosten, F (1999)
In prospective studies of acute uncomplicated, multidrug-resistant falciparum malaria on the western border of Thailand, the oral artemisinin derivatives were used alone in the treatment of 836 patients (artesunate 630, artemether 206), were combined with mefloquine (15-25 mg base/kg) in 2,826 patients, and mefloquine alone was used in 1,303 patients. The combined regimens of mefloquine plus an artemisinin derivative were associated with more side effects than those with an artemisinin derivative alone; acute nausea (31% versus 16%), vomiting (24% versus 11%), anorexia (51% versus 34%), and dizziness (47% versus 15%) (P < 0.001). Oral artesunate and artemether alone were very well tolerated. There was no difference in the incidence of possible adverse effects between the two drugs, and no evidence that either derivative caused allergic reactions, neurologic or psychiatric reactions, or cardiovascular or dermatologic toxicity. Blackwater fever occurred in three patients treated with mefloquine plus artesunate regimens. Oral artesunate and artemether are safe and well tolerated antimalarial drugs.